Cobalt phosphate nanoparticles decorated with nitrogen-doped carbon layers as highly active and stable electrocatalysts for the oxygen evolution reaction. Issue 21 (5th May 2016) - Yuan, Cheng-Zong; Jiang, Yi-Fan; Wang, Zhou; Xie, Xiao; Yang, Zheng-Kun; Yousaf, Ammar Bin; Xu, An-Wu
Abstract : We develop a facile method to prepare cobalt phosphate nanoparticles coated by N-doped carbon layers for highly active and stable OER electrocatalyst. Abstract : One promising approach to the production of clean hydrogen energy from electrochemical water splitting mainly relies on the successful development of earth-abundant, highly efficient and stable electrocatalysts for the oxygen evolution reaction (OER). Herein, we report the synthesis of robust cobalt phosphate nanoparticles (NPs) decorated with nitrogen-doped carbon layers (denoted as Co3 (PO4 )2 @N-C) using O -phospho-dl -serine as both phosphate and carbon sources by hydrothermal treatment. The obtained Co3 (PO4 )2 @N-C catalyst exhibits a remarkable electrocatalytic performance for the OER in alkaline media. A current density of 10 mA cm −2 is generated at a overpotential of only 317 mV with a small Tafel slope of 62 mV per decade in 1 M KOH electrolyte, which is even superior to those of state-of-the-art noble metal catalysts such as benchmark IrO2 catalysts. Notably, the Co3 (PO4 )2 @N-C electrode shows excellent stability evaluated by 1000 potential cycles and operation with a high current density at a fixed potential for 8 h, which is highly desirable for a promising electrocatalyst. The excellent activity can be attributed to the unique network structure of materials, a large number of active sites and good conductivity under catalytic conditions. Our findings imply the possibility for the development of robust and cost-efficient cobalt phosphate as a promising candidate to replace high-cost and scarce noble metal catalysts for electrochemical water splitting.